MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA SMP MELALUI PENDEKATAN PROBLEM BASED LEARNING - Rohmah, Ghina Sayyidah; Mahardika, Nurra Gina; Setiawan, Wahyu (IKIP Siliwangi, 2018)
This research uses classroom action research consisting of planning, action implementation, observation and evaluation, and reflection. The aim is to improve the mathematical connection ability of junior high school students through Problem Based Learning approach in class VIII-A SMP Darul Falah on Linear Two Variable Equation System. The instrument in this research is a description test of mathematical connection capability with three stages: initial test (before action), cycle test I and II (after action). The results showed the achievement of students' mathematical connection ability on the material of Linear Equation System Two Variables in grade VIII-A students of SMP Darul Falah can be improved through Problem Based Learning approach.